Métodos de la ciencia regional aplicables a la planificación regional - Moore, Frederick T. (1959)
The authors, summarily expose some of the most promising methods in the matter of regional science, applicable to regional planning: a) Gravitation models, represented in mathematical terms, to be able to solve practical questions; b) Linear program, with which may be identified the series of products of different industries that can increase actual "per capita" income of a region to highest degree; c) Analysis of an industrial sector, of a technics, similar to that employed when comparative costs are analyzed to determine the location of one industry; to end with a more detailed commentary of the; d) Cost- product method, which though admits, as others, industrial relations, considers them from a different point of view, marking some extensions of it, able to face dynamic problems in the analysis of economic fluctuations and in projections of economic increase.